A LITERATURE ANALYSIS ON 14 CASES OF ALLERGIC SHOCK CAUSED BY SAFFLOWER INJECTION - Sun, Zhengao; Lian, Fang; Zhang, Jianwei; Sun, Jinlong; Guo, Ying; Zhang, Ying (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to investigate the characteristics and general rules of domestic safflower injection causing allergic shock, to retrieve the medical journals published domestically, and to make statistical analysis on the cases of allergic shock caused by safflower injection. Results showed that the incidence of allergic shock caused by safflower injection in patients above 40 years old was high: females were more than males. It occurred within 30min after medication, and no patient died after emergency treatment. The study concluded that allergic shock caused by safflower injection is related to many factors, and clinical care personnel should pay more attention to it.